Trafficking in Human Possibilities - McRae, Jacquie (Auckland University of Technology, 2016)
A Chair in the Square is the draft of a literary novel, which is the creative component required for Masters of Creative Writing. It is accompanied by the exegesis: Trafficking in human possibilities. The exegesis will elucidate the creative work and provide an overview of the process employed in the writing of A Chair in the Square. Trafficking in human possibilities explores narrative patterns and investigates the universal characteristics of storytelling. A Chair in the Square is a tandem narrative novel with multiple protagonists, and interweaving threads. It is a modern day tale of wounded individuals set in a medieval village. A Chair in the Square is a novel that illuminates the idea that the stories we have been told, and that we tell ourselves, create the world we live in.
Keywords: Universal characteristics of storytelling; Narrative patterns